Preclinical and clinical research on bone and cartilage regenerative medicine in oral and maxillofacial region. Issue 2 (9th April 2014) - Takato, Tsuyoshi; Mori, Yoshiyuki; Fujihara, Yuko; Asawa, Yukiyo; Nishizawa, Satoru; Kanazawa, Sanshiro; Ogasawara, Toru; Saijo, Hideto; Abe, Takahiro; Abe, Masanobu; Suenaga, Hideyuki; Kanno, Yuki; et al.
Abstract: Recently, there have been remarkable advances in regenerative medicine, and almost all disorders of the oral and maxillofacial region could be research targets of regenerative medicine. Meanwhile, treatment in this region has been well established using biomaterials, prostheses, and microsurgery. Therefore, to surpass such a conventional approach as an alternative, regenerative medicine should take an approach of being less invasive and/or more effective. In this report, we present our preclinical and clinical research on bone and cartilage regenerative medicine in the oral and maxillofacial region. Regarding bone regenerative medicine, we have tried to develop artificial bone that would maximize bone formation at the transplanted site, but would subsequently be replaced by autologous bone. We have made custom‐made artificial bone (CT‐Bone) using alpha‐tricalcium phosphate (α‐TCP) particles and an ink‐jet printer, and have conducted clinical research and trials on 30 patients. To develop tissue‐engineered cartilage with proper three‐dimensional (3D) morphological form and mechanical strength, we have optimized the culture medium of chondrocytes and the scaffold. Following a preclinical study confirming efficacy and safety, we have conducted clinical research in three patients with nasal deformity associated with cleft lip and palate, and are now starting multicenter clinical research.